Produção integrada de D-tagatose a partir de lactose através da Co-imobilização de L-arabinose isomerase e β-galactosidase em agregados enzimáticos magnéticos reticulados. - Almeida, Ana Carolina Pinto de (2024)
D-tagatose is a sweetener that has 90% sweetness and low caloric value, compared to sucrose, does not increase blood sugar levels and has antidiabetic, probiotic and antioxidant characteristics. D-tagatose can be obtained by the enzymatic method, using L-arabinose isomerase (L-AI) as a biocatalyst, from the isomerization of D-galactose, a monosaccharide that can be obtained through the hydrolysis of lactose using the enzyme β- galactosidase (β-GAL). However, to maintain greater thermal and operational stability, maintaining better performance of biocatalysts in adverse operating conditions, enabling the recovery and reuse of enzymes, enzymatic immobilization methods can be applied, in which cross-linking by molecules of protein without the presence of a support, the formation of CLEAs (Cross-linked enzyme aggregates), whose methodology allows combining, in a single aggregate, two or more enzymes (Combi- CLEAs), presenting high productivity and reducing the cost of the biocatalyst and when enriched with magnetic characteristics (m-CLEAs), they allow the separation of aggregates using magnets. The objective of this work, therefore, was to study the co- immobilization of the enzymes β-GAL and L-AI in cross-linked magnetic enzymatic aggregates for the synthesis of the sugar D-tagatose from commercial lactose. To this end, this work was carried out in two main stages: (I) production of L-AI by submerged cultivation and (II) preparation of m-CLEAs and m-Combi-CLEAs. The growth of the microorganism, for the production of the LA-I enzyme, was evaluated in (a) shaken flasks (orbital shaker) and in (b) a benchtop bioreactor. The cellular growth of the microorganism was monitored in a culture medium containing whey lactose as an inducer for enzyme production. The use of yeast extract in analytical and industrial grade was also evaluated for comparative purposes. In (a) tryptone was not added to the medium, observing the impact on L-AI production. In (b) aerobic and anaerobic conditions were compared. After 12 hours of cultivation at 37 ºC and shaking at 200 RPM, cell disruption was carried out to obtain the enzymatic extract, which was characterized in terms of enzymatic activity, protein concentration and D-tagatose synthesis. For the production of D-tagatose from lactose, we started with the preparation of m-CLEAs from β-GAL, using the commercially available enzyme from Aspergillus oryzae. The hydrolysis capacity of m-CLEA from β-GAL was evaluated in the presence of 500 mM lactose. Then, m-CLEAs from L-AI, obtained in this work, were produced, as well as m-Combi-CLEAs containing both co-immobilized enzymes. The results of the experiments demonstrated that industrial yeast extract is a potential substitute for analytical grade yeast extract. It was also observed that the non-addition of tryptone impaired the growth of the microorganism but did not affect the production of the enzyme. The positive influence of aeration on the growth and production of the enzyme of interest was observed, impacting the amount of D-tagatose produced. Finally, an immobilization yield of 100% was observed for the CLEAs produced, with a lactose conversion of around 99.9%, when m-Combi-CLEA was used, and a bioconversion of D-tagatose around 16%.